Pleistocene and Recent Foraminifera from the Chukchi Rise and Canada Basin Areas of the Arctic Ocean. - Fagerlin,Stanley Charles (1971)
Two cores of Arctic Ocean sediments were studied to determine their faunal content. Emphasis was placed on the benthonic Foraminifera and their usefulness in paleoecologic considerations. Relative abundances were determined and species were identified. Master's thesis.